The Role of Mullay Gawra in an Education and Social Change - پرۆفیسۆرى یاریدەدەر دکتۆر عەبدوڵاڵ ڕهسوڵ نەژاد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Education as a cornerstone of the family and community is a long and continuous process with different aspects, fields, methods and goals that will fit into the cognitive system and the ideology of the society. And various factors, including language and literature, are involved in its development. The issue of education in the Kurdish community, like other aspects of life, is influenced by three important sections of national, religious and modern culture, and its national and religious characters are influential in it. Among these characters is a well-known thinker and reformer from Kooyeh city who eliminated superstition from Islam with a proper understanding of national culture, like other reformers of the Islamic world and was able to bring religion closer to contemporary understanding and to invite the young generation of Kurdish society to knowledge and patriotism, and to call for Godliness and could take effective proceedings to transform society by a brave fight with ignorance and superstition, and insisting on the rights of women as the teachers and educators of the new generation and also by practical actions such as setting up a school and sending her daughter to. This research has been done by descriptive-analytic method and has shown his important role in the education and developments of the Kurdish community by extracting some principles and methods of education from the works of this highly educated scientist.